What's in a Tibetan name? - Thupten Wodzer (Names)
Toponyms of the Tibetan Plateau have been scarcely studied. To help address that need, this study explores cross-cultural toponymy and phonetic opacity. The investigation focuses on toponyms containing the Tibetan word བྱ tza ‘bird’ that are used in Yulshul County in the Sanjiangyuan National Park, Qinghai Province. The research is based on personal interviews with 56 respondents and analyzing transliterations of bird-related toponyms for river, valley, and mountain names. Additionally, bird watching was used to gain important environmental insights. Twenty-nine bird-related toponyms were discovered and 59 bird species were recorded in the valley. There was no shared cognitive understanding of the toponyms Bird River and Bird Trace Valley.  It is speculated that this result may be due to the coupling effect of pronunciation nuance in the local Tibetan dialect and misleading transliterations in Chinese. Overall, the findings tentatively suggest the systematic and consistent Chinese transliteration of local Tibetan toponyms related to birds is important for keeping the connotations of these toponyms alive.